The Traf2DNxBCL2-tg Mouse Model of Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma Recapitulates the Biased IGHV Gene Usage, Stereotypy, and Antigen-Specific HCDR3 Selection of Its Human Counterpart - Perez-Chacon, Gema; Zapata, Juan M. (Frontiers in Immunology, 2021)
Chronic lymphocytic leukemia (CLL)/Small lymphocytic lymphoma (SLL) is a heterogeneous disease consisting of at least two separate subtypes, based on the mutation status of the immunoglobulin heavy chain variable gene (IGHV) sequence. Exposure to antigens seems to play a role in malignant transformation and in the selection and expansion of more aggressive CLL clones. Furthermore, a biased usage of particular IGHV gene subgroups and the existence of stereotyped B-cell receptors (BCRs) are distinctive characteristics of human CLL. We have previously described that Traf2DN/BCL2 double-transgenic (tg, +/+) mice develop CLL/SLL with high incidence with aging. In this model, TNF-Receptor Associated Factor (TRAF)-2 deficiency cooperates with B cell lymphoma (BCL)-2 in promoting CLL/SLL in mice by specifically enforcing marginal zone (MZ) B cell differentiation and rendering B cells independent of BAFF for survival. In this report, we have performed the sequencing of the IGHV-D-J rearrangements of B cell clones from the Traf2DN/BCL2-tg+/+ mice with CLL/SLL. The results indicate that these mice develop oligoclonal and monoclonal B cell expansions. Allotransplantation of the oligoclonal populations into immunodeficient mice resulted in the preferential expansion of one of the parental clones. The analysis of the IGHV sequences indicated that 15% were mutated (M) and 85% unmutated (UM). Furthermore, while the Traf2DN/BCL2-tg-/- (wild-type), -/+ (BCL2 single-tg) and +/- (Traf2DNDN single-tg) littermates showed the expression of various IGHV gene subgroups, the CLL/SLL expanded clones from the Traf2DN/BCL2-tg+/+ (double-transgenic) mice showed a more restricted IGHV gene subgroup usage and an overrepresentation of particular IGHV genes. In addition, the HCDR3-encoded protein sequence indicates the existence of stereotyped immunoglobulin (Ig) in the BCRs and strong similarities with BCR recognizing autoantigens and pathogen-associated antigens. Altogether, these results highlight the remarkable similarities between the CLL/SLL developed by the Traf2DN/BCL2-tg+/+ mice and its human counterpart.